Strategic engagement: new models of relationship management for academic librarians - Eldridge, Jeanette; Fraser, Katie; Simmonds, Tony; Smyth, Neil (Taylor & Francis, 2016)
How do we best bridge the gap between the Library and the diverse academic communities it serves? Librarians need new strategies for engagement. Traditional models of liaison, aligning solutions to disciplines, are yielding to functional specialisms, including a focus on building partnerships. This paper offers a snapshot of realignment across the Russell Group from subject support to relationship management. It then follows the journey of a newly-formed Faculty and School Engagement Team. Techniques are explored for building relationship capital, anchored to a model Strategic Engagement Cycle. Theory is contrasted with the challenges of securing real buy-in to new ways of working amid diverging agendas and assumptions, notably within the Library itself. Consideration is given to the retention of aspects of subject librarian roles. Investment in a relationship management function demands staunch and ongoing commitment to fulfil its promise, not only from its performers but from across the library community.